230 Body image seen by patients with nasopharyngeal cancer - Fares, Houda; Taouchikht, Mona; Abdou, Sara; Gueddari, Rania El; Ngbwa, édith Tatiana; Hassnaoui, Imane; Nouni, Karima; Lachgar, Amine; Elkacemi, Hanan; Kebdani, Tayeb; Hassouni, Khalid (Radiotherapy and oncology, 2024)
nasopharyngeal cancer often involves heavy treatment based on radio-chemotherapy which can affect the body image of patients, however,this parameter is often neglected by health professionals and its impact can be devastating. Evaluate body image in patients with cavum cancers at different times during treatment. This is a descriptive cohort study assessing body image that included 30 patients treated between January and March 2022. For cavum cancer. The Body Image Scale (BIS) was used for this assessment. A high score reflected an alteration in body image. The average age was 45 years (20-65 years) with a sex ratio of 2.5. The majority of patients were married, of urban origin (17 patients; 56%) and of primary education level (15 patients; 50%). The tumor stage (III) was the most represented (24 patients; 80%); the questionnaire was carried out during treatment for 20 patients (66%) Before treatment for 5 patients (16%) and in the first 6 months of follow-up for 5 patients (16%); 2 patients had a recurrence of the disease (6%). Patients presented functional symptoms related to cancer or treatments in 90% (27 patients). The most common symptoms were: dysphagia (15 patients), xerostomia (8 patients), hair loss and dysgeusia (6 patients) and fatigue, pain and burning sensations in 5 patients. These symptoms bothered the patients in 90% of cases (27 patients) and had caused a negative psychological impact in 66% of cases (20patients); 8 patients (26%) expressed an avoidance of the mirror, felt less attractive and believed they were victims of mutilating treatment. 10 patients (33%) expressed social avoidance and discomfort with themselves and 7 patients expressed a lack of self-confidence (23%) and discomfort with their partner (20%). 13 patients felt depressed (43%), however 17 patients felt optimistic (56%) and no patients expressed suicidal thoughts. All patients claimed to have a containing family and 13 patients (43%) complained of a negative impact on the profession. 14 patients used camouflage objects (46%), the most frequent of which: a scarf in 8 patients and a cap or hat in 6 patients, the average BSI score was 17 (10-37). Screening for altered body image in patients with cavum cancer seems to be essential by all health professionals, which helps improve the quality of life of patients.